(untitled) (American Journal of Islam and Society, 1998)
“ . . . a form of secular intellectual arrogance which, even while it cannot claim absolute certainty for a particular hypothesis, deems its findings superior to the content of religious truth.” (p. 267) David Waines, Introduction to Islam (Cambridge: Cambridge University Press, 1995). x + 332 pp. (hardback). Following the recent events in the Muslim world, bookshops have been flooded by works on the subject of Islam. On examination, it becomes clear that very few authors are willing, or indeed able, to write about the cultural phenomenon of the Islamic religion. Waines shows with his Introduction to Islam that he is one of those few. The approach taken in the book raises important methodological issues for the study of Islam and religion in general. Waines’s phenomenological approach raises doubt about the validity of a purely secular account of Islam which attempts to be “value-free.” The author is on the right track in terms of a social anthropological perspective in saying, “Religion is not a thing, but a happening, and it is people who make things happen.” This reminds the reader that Islam too has to be understood within its social and historical manifestations. In general, Waines portrays Islam in accordance with the phenomenological approach, from the traditional Muslim standpoint, and leaves the readers to judge Islam for themselves. In the introduction he states “It seemed more appropriate to present the Qur’an and the Prophet Mohammed as Muslims might recognize them, rather than as others have described them.” It is in this approach that he generally breaks with ...